PAMAM/5-fluorouracil drug conjugate for targeting E6 and E7 oncoproteins in cervical cancer: a combined experimental/in silico approach. Issue 9 (17th January 2017) - Rengaraj, Arunkumar; Subbiah, Balaji; Haldorai, Yuvaraj; Yesudhas, Dhanusha; Yun, Hyung Joong; Kwon, Soonjo; Choi, Sangdun; Han, Young-Kyu; Kim, Eung-Soo; N., Hema Shenpagam; Huh, Yun Suk
Abstract : In the present study, poly(amidoamine)/5-fluorouracil (PAMAM/5-FU) was used as a conjugate system for delivering drugs to target E6 and E7 oncoproteins, which are predominant in cervical cancers. Abstract : In the present study, poly(amidoamine)/5-fluorouracil (PAMAM/5-FU) was prepared and used as a conjugate system for delivering drugs to target E6 and E7 oncoproteins, which are predominant in cervical cancers. Specifically, molecular docking analysis was used to investigate the interaction between the PAMAM/5-FU and E6/E7 oncoproteins, which showed that the PAMAM/5-FU conjugate had a higher affinity for the oncoprotein than for 5-FU. Different generations of PAMAM dendrimers (0.5G, 1.0G, 1.5G, 2.0G, and 2.5G) were synthesized, characterized and tested as drug carriers for 5-FU. The PAMAM and PAMAM/5-FU drug conjugate showed less toxicity over COS-7 and HeLa cell lines. Laser confocal imaging and western blotting for tumor suppressor proteins pRb and p53 were used to confirm the interaction of PAMAM/5-FU with E6/E7 oncoproteins. Hematological analysis of PAMAM/5-FU using BALB/c female mice with cervical cancer confirmed the less toxic nature of this material. Based on these results, the developed PAMAM/5-FU conjugate is a potential candidate for the treatment of cervical cancer.